Efektivitas Pembelajaran Berbasis Gamifikasi Leaderboard dalam Meningkatkan Motivasi dan Pemahaman Siswa terhadap Materi Aqidah Akhlak Siswa di MTs Negeri 1 Bandung - Makmun, Syukron; AS, Suwarno (ARZUSIN, 2025)
One of the approaches that is increasingly popular in the world of education is gamification. Gamification is the application of game elements in the learning process with the aim of increasing student engagement, motivation, and understanding. The purpose of this study is to analyze the extent to which leaderboard gamification can increase student learning motivation, measuring its impact on the understanding of the concept of Aqidah Akhlak. This study uses a quasi-experimental method with a pretest-posttest control group design to measure the effectiveness of leaderboard-based gamification learning in increasing students' motivation and understanding of Aqidah Akhlak material at MTs Negeri 1 Bandung. The results of this study showed that the average student comprehension score in the experimental group increased by 23.5%, from an average of 65.2 in the pretest to 88.7 in the posttest. Meanwhile, the control group only increased by 9.8%, from an average of 64.8 to 71.2. In addition, observations of student activeness showed that the experimental group was more active in asking questions (12.4 times compared to 5.7 times in the control group), interacting with teachers (9.8 versus 4.3), and participating in discussions (15.2 versus 7.1). This data confirms that leaderboard gamification can increase students' active participation in the learning process. In addition to increasing understanding and activeness, leaderboard gamification also affects student discipline and involvement in learning. The results of the observation showed that the task completion rate of students in the experimental group reached 94.5%, much higher than the control group which was only 76.8%. In addition, the student attendance rate in the experimental group was also higher, at 98% compared to 92% in the control group. This data shows that the application of gamification not only has an impact on academic comprehension, but also on aspects of discipline and student learning motivation. Thus, leaderboard gamification can be used as an innovative learning strategy that supports improving the quality of education in madrasas.